The complete mitochondrial genome of Cheilinus trilobatus (Perciformes: Labridae). Issue 1 (2nd January 2023) - Wang, Teng; Li, Yupei; Ma, Qin; Liu, Yong; Xiao, Yayuan; Wu, Peng; Lin, Lin; Li, Chunhou
Abstract: Cheilinus trilobatus Lacépède, 1801 is a species of genus Cheilinus . In this study, we sequenced the complete mitochondrion genome of C. trilobatus . The mitochondrial genome was 17, 292 bp, consisting of 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and one non-coding control region (D-loop). The nucleotide composition was 27.31% A, 25.1% T, 17.23% G, and 30.36% C. Phylogenetic analysis suggested that C. trilobatus was closely related to Cheilinus oxycephalus . The complete mitogenome of C. trilobatus provided basic data for the genetic diversity conservation of this species.